Remoção forçada em área urbana e a resolução não adversarial - Ferreira, Antonio Rafael Marchezan (2016)
The present work analyzes forced evictions occurred in urban area, result of demands of judicial orders in re-possession actions and in ownership disputes, filed against population living in unplanned and unserviced settlements, with the aim of evaluating Brazilian jurisdictional management of such demands and mapping the ways to non-controversial adjust of conflicts. To that, we firstly present a panoramic view of forced eviction, approaching the terminology varieties and their respective semantic load; the forced eviction essential elements; its different levels of impact on affected population and respective instruments of evaluation of such impact and the main international normative references applicable to forced evictions, in order to detect its submission to juridical discipline of human rights, as well as the reception of these rules by Brazilian legal order. Secondly, we analyze the main features of the Brazilian urbanization process, so as to identify its responsibility concerning intensification of forced evictions practices in urban areas, pursuing, in this context, an examination on figures of forced eviction – quantitative data collected in reports which point to information on this practice in global scale – and the role of socio spatial segregations as a meaningful trait in Brazilian urbanization, being this reading performed with the contribution of literature about geographic space production. Thirdly, we evaluate how much Brazilian urban legal order contributes to establish a normative set applicable to forced eviction, by considering internationalization of rules related to forced eviction; urban law; and the re-reading of the right to property, with the break of the paradigms of classic civilism and the dialogue between urban legislation and socio spatial segregation. From then onwards, we study the jurisdictional management of forced evictions in urban areas, searching to detect gradual internalization of this urban-juridical order in the context of judicial decisions. To that, we approached juridical formalism of jurisdictional protection provided in tenure demands; the elements to build proper procedural technique to collective demand on tenure; the new Procedural Civil Law and the forced eviction, and the analysis of modern decisions in conflicts that can potentially promote forced eviction. We then identify ways of dialogue in conflicts of forced eviction in urban areas, as well as how certain theoretical assumptions are regarded, such as juridical pluralism and the consequent reorientation concerning the approach of conflicts of forced eviction; conflict management under the so called paradigm of complexity and its analysis from certain structural elements and juridical efforts to actualize the non-controversial management of conflicts of forced eviction. Finally, we propose methodological ways to non-controversial jurisdictional management of such conflicts, under the transformative perspective, discussing the following themes: social actors; multiple possibilities of consensual practices; the third-party facilitator and the procedural steps to build spaces for dialogues